ANTIDIABETIC AND ANTIHYPERLIPIDEMIC ACTIVITY OF DRACAENA CINNABARI BALF. RESIN ETHANOLIC EXTRACT OF SOQATRA ISLAND IN EXPERIMENTAL ANIMALS - Al-Baoqai, Nahed; Al-Mahbashi, Hassan; Al-Adhal, Adnan (Universal Journal of Pharmaceutical Research, 2018)
Objective: Dracaena cinnabari balf is a species plant in Abalfurn 1984e de la p pharmaciegavaceae family. It is a tree endemic to the Island of Socotra, Yemen. It was used as a dye and medicine in Socotra and the Mediterranean basin. Some researches demonstrated both hypoglycemic and hypolipidemic of its resin of Dracaena cochinchinensis, a traditional Chinese tree. Accordingly, this study aimed to evaluate the antidiabetic potential of the ethanolic extract of Dracanea cinnabari balf resin (DCBR), endemic in Socotra Island, in Alloxan induced diabetes, and evaluation of possible antihyperlipidemic activity of the same extract in high-cholesterol diet-induced hyperlipidemia in male albino rats. Methods: Experimental diabetes was induced in rats with intraperitoneal injection a single dose of Alloxan (150 mg/Kg). Hyperlipidemia was induced in rats by administration of 1% cholesterol in diet and 0.5 % Hydrogen Peroxide in drinking water for 14 days. Fasting blood glucose levels were measured at 1st day, 7th day and 14th day. Pancreas histopathology was done at the end. Estimation of serum lipid profile and liver histopathology was done at the end of 14 day. The results were expressed as mean±SD and differences among the groups of animals were compared using one-way ANOVA. Results: Administration of ethanolic extract of resin of two doses (100 and 300mg) in alloxan induce diabetic rats resulted in a significant decrease in FBG levels with a recovery in destruction of pancreas cell compared with untreated group .Also the same doses of extract showed significant decrease in triglycerides, total cholesterol, low density lipoprotein, very low density lipoprotein and Atherogenic index in comparing with untreated group. Conclusion: From the results of present study we can conclude the ethanolic extract of Dracaena cinnabari Balf. have a hypoglycemic and hypolipidemic activity in experimental animals , these activity are time and dose dependent. Peer Review History: Received 5 August 2018; Revised 19 September; Accepted 29 October, Available online 15 November 2018 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewer(s) detail: Dr. Rana Ahmed MohamedEl-Saied El-Fitiany , Ahram Canadian University, Giza, Egypt, marmarelfitiany@gmail.com Dr. Mohamed Derbali , Faculty of Pharmacy, Monastir, Tunisia, mohamed.edderbali@gmail.com